ANALISIS KEMAMPUAN BERPIKIR KRITIS SISWA DALAM MENYELESAIKAN MASALAH MATEMATIKA MELALUI MODEL PEMBELAJARAN PBL - Nisa, Khoirun (Program Studi Akuntansi IKOPIN, 2022)
Learning activities are very influential on the achievement of learning objectives. One of the lessons taught to students is learning mathematics. Viewed from the perspective of students, mathematics is a difficult material where students have to memorize formulas and count, but with the right and appropriate learning model, students are expected to be able to understand, analyze, and solve problems related to mathematics appropriately through critical thinking. Critical thinking is a process involving personal experience, training, or abilities accompanied by decision making to explain information or a truth that can be implemented in the learning process by using a model that is something with a mathematical character, the PBL model can be in the learning process related to problems. and decision making so that it relates to critical thinking. The research subjects in this study were fourth grade students at Kebondalem Mojosari Elementary School. The instrument used in this study was a test question sheet.